# 42t^2-13tv-42v^2=

## Simple and best practice solution for 42t^2-13tv-42v^2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 42t^2-13tv-42v^2= equation:

Simplifying
42t2 + -13tv + -42v2 = 0

Reorder the terms:
-13tv + 42t2 + -42v2 = 0

Solving
-13tv + 42t2 + -42v2 = 0

Solving for variable 't'.

Factor a trinomial.
(6t + -7v)(7t + 6v) = 0

Subproblem 1Set the factor '(6t + -7v)' equal to zero and attempt to solve:

Simplifying
6t + -7v = 0

Solving
6t + -7v = 0

Move all terms containing t to the left, all other terms to the right.

Add '7v' to each side of the equation.
6t + -7v + 7v = 0 + 7v

Combine like terms: -7v + 7v = 0
6t + 0 = 0 + 7v
6t = 0 + 7v
Remove the zero:
6t = 7v

Divide each side by '6'.
t = 1.166666667v

Simplifying
t = 1.166666667v
Subproblem 2Set the factor '(7t + 6v)' equal to zero and attempt to solve:

Simplifying
7t + 6v = 0

Solving
7t + 6v = 0

Move all terms containing t to the left, all other terms to the right.

Add '-6v' to each side of the equation.
7t + 6v + -6v = 0 + -6v

Combine like terms: 6v + -6v = 0
7t + 0 = 0 + -6v
7t = 0 + -6v
Remove the zero:
7t = -6v

Divide each side by '7'.
t = -0.8571428571v

Simplifying
t = -0.8571428571vSolutiont = {1.166666667v, -0.8571428571v}`